Intrauterine growth standards: a cross-sectional study in a population of Nigerian newborns - Olugbenga A. Mokuolu; Omotayo O. Adesiyun; Mohammed B. Suleiman; Mustapha Bello (MDPI AG, 2012)
The aim of the study was to define an intrauterine growth curve for a population of Nigerian newborn babies. A cross-sectional observational study design was adopted. Weight, length and head circumference were all measured in consecutive singleton deliveries at the University of Ilorin Teaching Hospital over a 3-year period. Gestational age (GA) of the babies was estimated from the last menstrual period or first trimester ultrasound. The estimates obtained were clinically validated using the Ballard score. Mean birth weights and percentiles of the weight, length and head circumferences for the respective GA were estimated using the SPSS 15 software package. A total of 5273 babies were recruited for the study with GA ranging from 25-44 weeks. Comparison of the mean birth weights of the various GA with the data from Denver, Colorado, showed that Nigerian babes tended to weigh less at the early GA, although these differences were not statistically significant. Between 26-36 weeks, the average weights of both sexes were similar; however, beyond this time point there was a consistent increase in the average weight of the males over the female babies. Growth curves for Nigerian newborn babies were generated and showed that the mean birth weight of Nigerian preterm babies was lighter than that of babies in Colorado. The impact of these differences on the classification of newborns will require further evaluation.